2021
DOI: 10.5498/wjp.v11.i4.133
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of digital psychotherapeutic intervention among perinatal women: A systematic review and meta-analysis of randomized controlled trials

Abstract: BACKGROUND The perinatal period is a challenging time of substantial emotional, physiological, social, and relational changes. Depression, anxiety, and stress symptoms are common, and co-exist in the perinatal period. Digital technology continues to grow at an unprecedented pace with wide application, including psychotherapeutic intervention. A growing number of meta-analyses supported the application of digital psychotherapeutic intervention across different populations, but relatively few meta- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“… Sawyer et al (2019) reported sustained improvement in depression and parent-child bonding at four months follow-up while Shorey et al (2019) reported sustained improvement in parenting self-efficacy, anxiety, depression, social support, and parent-child bonding at two-months follow-up. A similar lack of follow-up assessments was reported by previous reviews ( Daly et al, 2018 ; Dol et al, 2020 ; Lau et al, 2021 ). While the currently limited data suggested the possibility of sustained positive effects of mobile application-based interventions on parents’ well-being for 2-4 months, the long-term effects of these interventions require further evaluation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“… Sawyer et al (2019) reported sustained improvement in depression and parent-child bonding at four months follow-up while Shorey et al (2019) reported sustained improvement in parenting self-efficacy, anxiety, depression, social support, and parent-child bonding at two-months follow-up. A similar lack of follow-up assessments was reported by previous reviews ( Daly et al, 2018 ; Dol et al, 2020 ; Lau et al, 2021 ). While the currently limited data suggested the possibility of sustained positive effects of mobile application-based interventions on parents’ well-being for 2-4 months, the long-term effects of these interventions require further evaluation.…”
Section: Discussionsupporting
confidence: 83%
“…This review found that studies that reported a significant improvement in anxiety or depression had included some form of psychotherapeutic element in their interventions such as mindfulness-based modules ( Prasad, 2018 ), cognitive behavioural therapy ( Jannati et al, 2020 ), and education about emotional health ( Sawyer et al, 2019 ; Shorey et al, 2019 ). Similarly, a previous review also reported the effectiveness of digital psychotherapeutic perinatal interventions in improving depression, anxiety, and stress among women ( Lau et al, 2021 ). Only two interventions that included a psychotherapeutic component reported no significant improvement in parents’ psychological well-being ( Baumel et al, 2018 ; Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Empirically-supported psychotherapies represent another first-line treatment option for pregnant women and mothers (35). Digital administration of psychotherapy, which was recently shown to reduce depression, anxiety, and stress during pregnancy and the postpartum period in a meta-analysis of randomized controlled trials, may increase accessibility and reduce barriers (36).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, systematic reviews of RCTs on maternal apps described the information for software and hardware, intervention content and delivery, and limitations. They still highlighted the risks of RTCs, such as unclear allocation concealment, no evaluation of objective quality in intervention apps, and no published protocols (20)(21)(22). Furthermore, studies reviewing apps that cover children's first 1,000 days of life (from conception to the age of 24 months) have exclusively focused on the prenatal or postnatal phases, ignoring the continuity between the two periods and their combined effect on the health of the mother and child (23,24).…”
Section: Introductionmentioning
confidence: 99%